2022
DOI: 10.1183/16000617.0095-2022
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of the neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio in acute exacerbations of COPD: present and future

Abstract: Acute exacerbations of chronic obstructive pulmonary disease (AECOPD) are a leading cause of hospitalisation and death in COPD patients. In addition to the identification of better strategies to prevent AECOPD, there is an intense focus on discovering novel markers of disease severity that enhance risk stratification on hospital admission for the targeted institution of aggressiveversussupportive treatments. In the quest for such biomarkers, an increasing body of evidence suggests that specific indexes derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 55 publications
1
21
0
1
Order By: Relevance
“…A previous narrative review discussed the relationship between NLR and the PLR on admission and several clinical endpoints in COPD 28 . That narrative review also demonstrated that NLR is a simple and inexpensive marker of inflammation that has been increasingly studied in several disease states, including COPD, and appears to be a promising predictor of mortality in COPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…A previous narrative review discussed the relationship between NLR and the PLR on admission and several clinical endpoints in COPD 28 . That narrative review also demonstrated that NLR is a simple and inexpensive marker of inflammation that has been increasingly studied in several disease states, including COPD, and appears to be a promising predictor of mortality in COPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…COPD is a chronic disease, followed by a slowly progressive natural course that can be accelerated by acute exacerbation, which was the leading cause of death in COPD patients. 50 Given that the acute exacerbation of COPD can be reversible by urgent or hospital treatment, COPD-specific death cases among COPD patients may be limited, which was insufficiently powered to find statistical significance. Besides, COPD patients with prediabetes, diabetes and longer diabetes duration showed higher HRs for COPD-specific death, but the result with wide confidence intervals crossing the null hypothesis suggests there is insufficient statistical power to provide significant conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for this is that the number of COPD‐specific death cases was insufficient to detect significant statistical power. COPD is a chronic disease, followed by a slowly progressive natural course that can be accelerated by acute exacerbation, which was the leading cause of death in COPD patients 50 . Given that the acute exacerbation of COPD can be reversible by urgent or hospital treatment, COPD‐specific death cases among COPD patients may be limited, which was insufficiently powered to find statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…11 The clinical condition known as acute exacerbation of chronic obstructive pulmonary disease (AECOPD) is characterized by a sudden deterioration of respiratory symptoms and airway function. 12 …”
Section: Methodsmentioning
confidence: 99%